Peningkatan Kreativitas Guru Melalui Pelatihan Media Pembelajaran Mathventure Berbantuan Komik - Sofri Rizka Amalia; Anwar Ardani; Dian Purwaningsih; Nida Hanifah; Intan Nuraeni (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Problems faced by schools include the use of conventional learning models, the lack of interactive learning media, some teachers using existing learning media available online, and inadequate infrastructure. Community service was conducted at SD Negeri 1 Taraban. The community service procedures included (1) preparation, (2) implementation, and (3) evaluation. Data analysis in this community service used normalized n-gain (g). The magnitude of the increase was measured using the N-Gain value. The results of the community service were the responses of training participants, measured through direct observation during the activity. Based on observations, 85% of participants responded positively. Teacher creativity increased with an average n-gain score of 0.43, in the moderate category.